Pengaruh Layanan Internet Banking, Mobile Banking, Dan Automatic Teller Machine (ATM) Terhadap Tingkat Kepuasan Nasabah Bank Syariah Di Indonesia (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Islam Angkatan 2019) - Hafidah Ayu Kusnadi; Nurbaiti Nurbaiti; Nursantri Yanti (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims to determine the influence of internet banking services,Mobile Banking, and Automatic Teller Machine (ATM) on Satisfaction Sharia Bank Customers in Indonesia (Case Study of Students from the Faculty of Economics and Islamic Business Class of 2019). This study uses a quantitative approach. In this study a questionnaire was used to collect data, and 97 Students at the Faculty of Islamic Economics and Business Class of 2019 were selected as sample using the Accidental Sampling method. Data analysis in research this is quantitative data analysis. Statistical tests are known as Regression Tests Multiple Linear, t-test, f-test, and Coefficient of Determination (R2) are all components of this analysis, and also tests of classical assumptions. Based on testing The hypothesis with the partial T test can be concluded that the internet banking variable mobile banking and ATM partially have a significant effect on satisfaction. Based on hypothesis testing with the Simulta F test, it can be concluded that internet banking, mobile banking and ATM variables together influence the level of satisfaction of Sharia Bank customers.